Gastrointestinal lesions in chronic kidney disease patients with anemia - Rebeca García Agudo; Sami Aoufi Rabih; Pedro González Carro; Francisco Pérez Roldán; Beatriz Proy Vega; Ángel Arias Arias; Fátima Cazalla Cadenas; José María Tenías Burillo; Ana Fernández Rodríguez (Nefrología (English Edition), 2019)
Introduction: Despite the frequency with which anemia is present in patients with chronic kidney disease (CKD), its relationship with gastrointestinal lesions has not been studied. Method: A cross-sectional, analytical, observational study involving one year of recruitment was carried out to determine the prevalence of endoscopic gastrointestinal lesions and associated risk factors in asymptomatic patients with chronic kidney disease stages 1–5 and anemia who had a positive qualitative immunochemical fecal occult blood test. Results: A total of 9658 patients with CKD were analyzed, of which 286 (2.9%) had anemia; 198 had a positive fecal occult blood test (47% male, 71.1 ± 11.8 years). The endoscopic study revealed 255 lesions, with at least one lesion in 68.2% of patients, with the most prevalent being: adenomatous colorectal polyps (39.6%), acute lesions of the gastric mucosa (22.6%), neoplastic lesions 15.1%), angiodysplasia (14.4%), oesophagitis (8.4%), inflammatory bowel disease (4.8%) and ischemic colitis (3.1%). Uremia and acetylsalicylic acid were identified as risk factors for acute gastric mucosal lesions. Angiodysplasia was associated with alcoholism, a more advanced stage of chronic kidney disease, anemia, and lack of response to erythropoiesis-stimulating agents. Age and refractory anemia were risk factors for adenomatous polyps and colorectal cancer. Conclusion: Renal patients with anemia could benefit from an endoscopic study due to their high prevalence of gastrointestinal lesions, particularly adenomatous polyps and colorectal cancer, which are more common in those over 50 years of age with CKD stages 3–5. Resumen: Introducción: A pesar de la frecuencia con que la anemia está presente en los pacientes con enfermedad renal crónica (ERC), su relación con lesiones gastrointestinales no ha sido estudiada. Método: Estudio observacional analítico transversal de un año de reclutamiento para determinar la prevalencia de lesiones gastrointestinales endoscópicas y los factores de riesgo asociados en pacientes asintomáticos con ERC estadios 1-5 y anemia que presentaban un test inmunoquímico cualitativo de sangre oculta en heces positivo. Resultados: Se analizaron 9.658 pacientes con ERC, de los que 286 (2,9%) presentaban anemia; 198 tuvieron un test de sangre oculta en heces positivo (47% varones, 71,1 ± 11,8 años). El estudio endoscópico reveló 255 lesiones, con al menos una lesión en el 68,2%, siendo las más prevalentes: pólipos colorrectales adenomatosos (39,6%), lesiones agudas de la mucosa gástrica (22,6%), lesiones neoplásicas (15,1%), angiodisplasias (14,4%), esofagitis (8,4%), enfermedad inflamatoria intestinal (4,8%) y colitis isquémica (3,1%). La uremia y el ácido acetilsalicílico fueron identificados como factores de riesgo de lesiones agudas de la mucosa gástrica. Las angiodisplasias se relacionaron con el enolismo, el mayor estadio de ERC, la anemia y la ausencia de respuesta a agentes estimulantes de la eritropoyesis. La edad y la anemia refractaria constituyeron factores de riesgo de pólipos adenomatosos y cáncer colorrectal. Conclusión: Los pacientes renales con anemia podrían beneficiarse de un estudio endoscópico debido a la alta prevalencia de lesiones gastrointestinales que presentan, particularmente pólipos adenomatosos y cáncer colorrectal, más frecuentes en los mayores de 50 años con ERC estadios 3-5. Keywords: Chronic kidney disease, Anemia, Colorectal cancer, Adenomatous polyps, Acute lesions of the gastric mucosa, Palabras clave: Enfermedad renal crónica, Anemia, Cáncer colorrectal, Pólipos adenomatosos, Lesiones agudas de la mucosa gástrica